HOUSING IN TRANSIT. Which transition for the industrialised public housing? - Marina Block; Roberto Ruggiero (Techne)
The paper reflects possible “transition” strategies for the industrialised residential building stock considering its systemic nature and current technological availability, with particular reference to digital technologies. Screening of some research on housing in the context of ecological and digital transition is proposed, starting from a critical review of interventions over the past decades, which reveal a fragmented framework of punctual solutions that cannot be codified as organic and replicable strategies. This highlights the research world’s focus on broader holistic approaches that look at energy transition as closely related to the transition of the entire building organism and the inhabiting community.